The roots of populism : neoliberalism and working-class lives - Elliott, Brian, 1941- (Manchester University Press, 2021)
A novel and highly engaging philosophical analysis of populism and how it represents both a challenge to and promise of renewal for liberal democracy. Elliott argues that neoliberal governance has sought to bury the legacy of working-class politics but now the reappearance of "the people" is causing a systemic crisis in liberal democracy.